PENGARUH METODE PERKULIAHAN ONLINE TERHADAP EFEKTIVITAS PEMBELAJARAN MAHASISWA ILMU HUKUM ANGKATAN 2019 - Esteria Pasaribu (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
The purpose of this research was to see how the online lecture method affected the learning effectiveness of students at the Raja Ali Haji Maritime University's Law Science class of 2019. Correlational research is a sort of hypothesis-driven study in which the variables evaluated are categorized according to the type of relationship they have. The authors of this study used samples from students at Raja Ali Haji Maritime University's Law Study Program class of 2019 who had attended online-based lectures throughout the Covid-19 timeframe. The Slovin algorithm was used to calculate the sample size in this study, which yielded 47 responses. Simple linear regression with a data processing package, such as SPSS, was utilized to analyze the data.